UNDERWATER DIVING TOURISM ON THE COASTS OF THE GULF OF SAROS - Okan YAŞAR (Zeitschrift für die Welt der Türken, 2011)
This study aims at revealing underwater diving tourism on the coasts of the Gulf of Saros in respect of various aspects. Underwater diving tourism on the coasts of the Gulf of Saros has made a parallel progress to the coastal tourism. Underwater diving tourism on the coasts of the Gulf of Saros is the most important tourism variety on which is put emphasis so that tourism season may extend and tourism may acquire an international dimension. In the survey, the geographical factors which affect the underwater diving tourism, the motivations which create and glamorousness, the diving locations and characteristics on the Gulf of Saros have been dealed. On the other hand, in the survey carried out and the problems experienced have been examined extensively so that the development of the underwater diving tourism in the Gulf of Saros may acquire an international dimension. Finally, suggestions and recommendations are made so that the elements that create charm and fascinations may be protected in underwater diving tourism of the coasts of the Gulf of Saros and underwater diving tourism may be developed considerably.